Peningkatan Profesionalisme Dosen IBI Kosgoro 1957 Melalui Pelatihan Distance Learning System Menggunakan Google Meet - Wihandar, Asep Mulyana; Kurniawan, Ari (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2020)
Education is a process to improve student intelligence. This process uses training and teaching activities. Along with the development of technology and communication, the training and learning process uses various methods, one of which is e-learning. The process uses the internet, which can be accessed and processed anytime and anywhere. This process supports the policies of the Indonesian Ministry of Education and Culture regarding the learning process and approaching learning. This process can promote active, planned, and effective education. In addition, service and learning innovations are increasing so that they do not only use conventional learning. The purpose of this community service is to train lecturers at IBI Kosgoro 1957 in implementing e-learning using Google Classroom. The method of implementation uses theory and practice. The results of the training process can provide online learning innovations with Google Classroom, and the ability of teachers to implement them can improve the independent learning process. Teachers can carry out learning with virtual classes following the conditions of learning in the classroom. Classes built with Google Classroom can be used to share material, give assignments, quizzes, assign grades, and schedule activities. In addition, the video conferencing process adjusts the schedule in the classroom and calendar and calendar using meet.